2014
DOI: 10.1002/hbm.22616
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal resting state fMRI analysis in healthy controls and premanifest Huntington's disease gene carriers: A three-year follow-up study

Abstract: Based on the results found in this study, the provisional conclusion is that RS-fMRI lacks sensitivity in detecting changes in functional connectivity in HD gene carriers prior to disease manifestation over a 3-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
1
35
2
Order By: Relevance
“…Other studies on pre‐HD and early‐onset patients reported reduced rsFC . However, a longitudinal study of pre‐HD over a period of 3 years didn't detect change in rsFC despite a significantly higher rate of striatal atrophy . This is different from recently suggested correlated patterns of structural atrophy within resting state network deficits in several neurodegenerative diseases .…”
Section: Introductioncontrasting
confidence: 79%
“…Other studies on pre‐HD and early‐onset patients reported reduced rsFC . However, a longitudinal study of pre‐HD over a period of 3 years didn't detect change in rsFC despite a significantly higher rate of striatal atrophy . This is different from recently suggested correlated patterns of structural atrophy within resting state network deficits in several neurodegenerative diseases .…”
Section: Introductioncontrasting
confidence: 79%
“…VIS impairment prior to motor symptom onset is less clear. Most of the studies in pre‐HD did not report changes within this network compared to HC (Coppen et al, ; Odish et al, ; Poudel et al, ). Only Dumas et al () showed reduced connectivity in the medial VIS, in brain regions positioned outside the canonical visual mask (i.e., left frontal and right parietal lobules), leaving it unknown whether this connectivity pattern could reflect early changes within the VIS.…”
Section: Resultsmentioning
confidence: 99%
“…The auditory network did not show selective vulnerability at rest in either manifest or pre‐HD (Dumas et al, ; Odish et al, ; Poudel et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly reduced synchronization in the sensory-motor network, particularly in the medial primary motor area (M1) posterior to the supplementary motor area, was detected by another study23. Others have reported no difference to controls2425. Some studies have also shown correlations between disease burden and functional connectivity25.…”
Section: Discussionmentioning
confidence: 99%